2022
DOI: 10.3389/fmicb.2022.1063414
|View full text |Cite
|
Sign up to set email alerts
|

A diagnostic accuracy study comparing RNA LAMP, direct LAMP, and rapid antigen testing from nasopharyngeal swabs

Abstract: IntroductionDuring the coronavirus disease 2019 (COVID-19) pandemic, the early detection and isolation of individuals infected with severe acute respiratory syndrome coronavirus disease 2 (SARS-CoV-2) through mass testing can effectively prevent disease transmission. SARS-CoV-2 nucleic acid rapid detection based on loop-mediated isothermal amplification (LAMP) may be appropriate to include in testing procedures.MethodsWe used 860 nasopharyngeal specimens from healthcare workers of Huashan Hospital and COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…Although isothermal nucleic acid amplification and LAMP are comparable to RAT in terms of simplicity, convenience, and rapidity, their sensitivity and specificity are far more superior 19,21,22 . Based on our experience and according to various studies, false negative RAT results have been observed in samples with a low viral load, particularly in samples with a C T > 25 [23][24][25] .…”
Section: Discussionmentioning
confidence: 99%
“…Although isothermal nucleic acid amplification and LAMP are comparable to RAT in terms of simplicity, convenience, and rapidity, their sensitivity and specificity are far more superior 19,21,22 . Based on our experience and according to various studies, false negative RAT results have been observed in samples with a low viral load, particularly in samples with a C T > 25 [23][24][25] .…”
Section: Discussionmentioning
confidence: 99%
“…Reverse transcription loop-mediated isothermal amplification (RT-LAMP) assays have now also been developed for the diagnosis of SARS-CoV-2 [ 10 , 11 ]. RT-LAMP combines the advantages of Ag-RDTs as they are easy, rapid, and do not require specialized infrastructures [ 10 ] or real-time RT-PCR (high sensitivity) [ 10 , 11 , 12 , 13 ]. These properties make RT-LAMP an attractive candidate diagnostic test for implementation in LMICs.…”
Section: Introductionmentioning
confidence: 99%